2020
DOI: 10.1080/01652176.2020.1733704
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Brazilian wild-type strains of bovine respiratory syncytial virus reveals genetic diversity and a putative new subgroup of the virus

Abstract: 2020) Molecular characterization of Brazilian wild-type strains of bovine respiratory syncytial virus reveals genetic diversity and a putative new subgroup of the virus, Veterinary Quarterly, 40:1, 83-96, ABSTRACT Background: Bovine orthopneumovirus, formerly known as bovine respiratory syncytial virus (BRSV), is frequently associated with bovine respiratory disease (BRD). Aim: To perform the molecular characterization of the G and F proteins of Brazilian wildtype BRSV strains derived from bovine respiratory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…It is a protein that is central to virus entry into cells, as well as being responsible for the fusion of infected cells with adjacent cells, resulting in the formation of large multinucleated syncytia [ 28 ]. Furthermore, the F gene is also a highly conserved region of the BRSV genome compared with the G gene [ 11 ]. The results of partial sequencing of the F gene of the current three isolates revealed that they were 100% identical to each other and were closely related to the sequence submitted (KY499619) from Turkey by Timurkan et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a protein that is central to virus entry into cells, as well as being responsible for the fusion of infected cells with adjacent cells, resulting in the formation of large multinucleated syncytia [ 28 ]. Furthermore, the F gene is also a highly conserved region of the BRSV genome compared with the G gene [ 11 ]. The results of partial sequencing of the F gene of the current three isolates revealed that they were 100% identical to each other and were closely related to the sequence submitted (KY499619) from Turkey by Timurkan et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis based on both F and G proteins has led to a subdivision of BRSV into eight subgroups, denoted I–VIII [ 7 , 9 , 10 , 11 ]. These subgroups tend to separate geographically; subgroup I BRSV strains are typically isolated in the UK and Switzerland, whereas subgroup II normally includes strains from the Netherlands, Denmark, Belgium, France, and Japan [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the human respiratory syncytial virus, BRSV belongs to the genus Orthopneumovirus of the Pneumoviridae family and harbors an approximately 15 k bp-long single-stranded negative-sense RNA genome [ 7 , 8 ], which encodes 11 proteins including three surface glycoproteins (glycoprotein G, small hydrophobic protein SH, and fusion protein F), nucleoprotein (N), viral RNA-dependent polymerase protein (L), phosphoprotein (P), matrix protein (M), transcriptional anti-termination factor M2-1, RNA regulatory protein M2-2, and two nonstructural proteins, namely, NS1 and NS2 [ 9 , 10 ]. Since the 1990s, molecular-genetic characterization studies have revealed that the emergence of new variants manifests a geographic correlation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Several studies have used G sequences, and one study has used both G and F sequences to analyze genetic evolution of BRSV; these studies have shown that BRSV strains can be classified into 9 genetic subgroups, I–IX. 1,4,9,12 We used the G gene, in combination with information on the F gene, to analyze Japanese BRSV strains to obtain molecular epidemiologic characterization of the virus to provide genetic information for vaccine-based disease control.…”
mentioning
confidence: 99%